PGM3 inhibition shows cooperative effects with erastin inducing pancreatic cancer cell death via activation of the unfolded protein response - Zerbato, Barbara; Gobbi, Maximilian; Ludwig, Tobias; Brancato, Virginia; Pessina, Alex; Brambilla, Luca; Wegner, Andre; Chiaradonna, Ferdinando (Frontiers in Oncology, 2023)
Background Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive cancer with a poor patient prognosis. Remarkably, PDAC is one of the most aggressive and deadly tumor types and is notorious for its resistance to all types of treatment. PDAC resistance is frequently associated with a wide metabolic rewiring and in particular of the glycolytic branch named Hexosamine Biosynthetic Pathway (HBP). Methods Transcriptional and bioinformatics analysis were performed to obtain information about the effect of the HBP inhibition in two cell models of PDAC. Cell count, western blot, HPLC and metabolomics analyses were used to determine the impact of the combined treatment between an HBP’s Phosphoglucomutase 3 (PGM3) enzyme inhibitor, named FR054, and erastin (ERA), a recognized ferroptosis inducer, on PDAC cell growth and survival. Results Here we show that the combined treatment applied to different PDAC cell lines induces a significant decrease in cell proliferation and a concurrent enhancement of cell death. Furthermore, we show that this combined treatment induces Unfolded Protein Response (UPR), NFE2 Like BZIP Transcription Factor 2 (NRF2) activation, a change in cellular redox state, a greater sensitivity to oxidative stress, a major dependence on glutamine metabolism, and finally ferroptosis cell death. Conclusion Our study discloses that HBP inhibition enhances, via UPR activation, the ERA effect and therefore might be a novel anticancer mechanism to be exploited as PDAC therapy.